An Analysis of Slang Used on Prawirotaman Street, Yogyakarta - Agustinus Hary Setyawan; Afan Setiawan (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
This Paper discusses about the analysis of slang that is used by western tourist in Prawirotaman Street in Yogyakarta. The purpose of this study is to find out the types and meaning of slang primarily used by western tourists. It uses a qualitative description method where it describes slang that is used by western tourists. Theory of Eric Partridge (2004) in types of slang is used to indentify the slang. Three types of slang are commonly used by the western tourists on Prawirotaman Street, Yogyakarta and 15 reasons are found. Therefore, the research has implications for the reader to have and apply their knowledge about slang in informal context of daily communication especially in certain tourism area contexts. It also enriches reader’s linguistic feature that can enhance their communicative skills since the social functions of the language are learnt.